The Impact of Perkins and Blith Model on the Achievement of Second Grade Intermediate Students in the Subject of Social Studies (Journal of the College of Basic Education, 2020)
The present research aims to find out the "The Impact of Perkins and Blyth Model on the Achievement of Second Grade Intermediate Students in the Subject of Social Studies. To achieve this, the researcher chose the experimental design with partial control of the experimental and control groups. The research sample consisted of (80) students with (40) students in the experimental group and (40) students from the control group. The researcher balanced between the control group and the experimental group in several variables “prior knowledge, IQ test, the chronological age of the students calculated by months and the previous year's grades in history”. The researcher prepared an achievement test that consisted of (30 articles). The validity and stability of the test were verified. Furthermore, the researcher concluded that there is a statistically significant difference in favor of the experimental group and concluded that the model has positive effects and gives freedom for students to express their opinions. The experiment continued the second semester, which means a full semester of the academic year (2019/2018). As for data processing, the researcher used the SPSS Statistics package .